Distribution of Immune Cells Including Macrophages in the Human Cochlea - Liu, Wei; Danckwardt-Lillieström, Niklas; Schrott-Fischer, Anneliese; Glueckert, Rudolf; Rask-Andersen, Helge (Frontiers in Neurology, 2021)
Background: The human cochlea was earlier believed to lack capacity to mount specific immune responses. Recent studies established that the human cochlea holds macrophages. The cells appear to surveil, dispose of, and restore wasted cells to maintain tissue integrity. Macrophage activities are believed to be the central elements in immune responses and could swiftly defuse invading microbes that enter via adjacent infection-prone areas. This review updates recent human studies in light of the current literature and adds information about chemokine gene expression. Material and Methods: We analyzed surgically obtained human tissue using immunohistochemistry, confocal microscopy, and multichannel super-resolution structured illumination microscopy. The samples were considered representative of steady-state conditions. Antibodies against the ionized calcium-binding adaptor molecule 1 were used to identify the macrophages. CD68 and CD11b, and the major histocompatibility complex type II (MHCII) and CD4 and CD8 were analyzed. The RNAscope technique was used for fractalkine gene localization. Results: Many macrophages were found around blood vessels in the stria vascularis but not CD4 and CD8 lymphocytes. Amoeboid macrophages were identified in the spiral ganglion with surveilling “antennae” projecting against targeted cells. Synapse-like contacts were seen on spiral ganglion cell bodies richly expressing single CXC3CL gene transcripts. Branching neurite-like processes extended along central and peripheral axons. Active macrophages were occasionally found near degenerating hair cells. Some macrophage-interacting T lymphocytes were observed between the scala tympani wall and Rosenthal’s canal. CD4 and CD8 cells were not found in the organ of Corti. Conclusions: The results indicate that the human cochlea is equipped with macrophages and potentially lymphocytes, suggesting both an innate and adaptive immune capacity. A rich expression of fractalkine gene transcripts in spiral ganglion neurons suggest an essential role for auditory nerve protection, as has been demonstrated experimentally. The findings provide further information on the important role of the immune machinery present in the human inner ear and its potential to carry adverse immune reactions, including cytotoxic and foreign body responses. The results can be used to form a rationale for therapies aiming to modulate these immune activities.